THE PROBLEM OF ILLITERACY AMONG THE POPULATION OF FERGANA REGION IN THE 1920S–1930 S AND THE MEASURES AIMED AT ITS ELIMINATION - Nizomiddinov Odiljon Bakhodirovich (Sciental Journals Publishing, 2025)
The article analyses archival documents describing the state of the education system in Ferghana province in 1920–1930, issues of illiteracy, creation of new Soviet schools, etc. The article also describes the level of illiteracy in Ferghana province, measures to eliminate it in the archival documents of practical actions to increase the number of literate youth.
Keywords: Illiteracy